Palliative embolization arteries or veins for a recurrent pelvic chondrosarcoma - Biz, Carlo; Angelini, Andrea; Crimі Alberto; Trovarelli, Giulia; Igoumenou, Vasilios; Mavrogenis, Andreas; Ruggieri, Pietro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
Chondrosarcoma is a malignant bone tumor characterized by the formation of cartilage structures of varying degrees of maturity. They account for approximately 20 % of malignant skeletal tumors. Chondrosarcoma most often affects the pelvis (iliac bone), the proximal femur and humerus, ribs. The chondrosarcoma of the pelvis has a low response to chemo-and radiation therapy, so they are usually resected by standard hemipelvectomy. New surgical reconstructive techniques allow surgeons to perform major reconstructions, thereby improving patients’ quality of life. Clinical case: male, 64 years old, with complains of the left thigh pain for 6 months. The patient was made a comprehensive examination — standard X-rays, MRI and CT scan of the pelvis, biopsy of the pathological formation. Diagnosis: chondrosarcoma II clinical group, stage IIB. Primary surgery — wide-field excision and reconstruction with a massive bone allograft was performed and bipolar hip replacement. Two major local recurrences were detected in 3 years. Due to inefficiency of chemo-and radiation therapy, refusal of the patient from amputation, high degree of tumor vascularization, arterial embolization was applied. A selective study of both the medial and lateral femoral arteries was performed using a uroangiographic contrast medium. The achievement of complete devascularization of the greatest lesion was confirmed angiographically. After 20 days due to partial revascularization, re-embolization of the lateral circular femoral artery was made. The final embolization of all arterial branches that fed the tumor was performed after 3 months with acrylic (n-butyl 2-cyanoacrylate) glue for larger-sized vessels and microparticles of polyvinyl alcohol (150–250 μm) for the smallest branches. Conclusion: embolization can be effectively used as a palliative treatment for highly vascularized pelvic chondrosarcoma.